Survei Pengetahuan Atlet Bola Voli Mengenai Penanganan Pertama Cedera Olahraga Metode RICE - Nasya Amara Dewi; Bimo Alexander; Andri Arif Kustiawan; Agus Pribadi (MAN Insan Cendekia Jambi, 2026)
Timely first aid for sports injuries is crucial to minimize the risk of tissue severity. This descriptive quantitative study aims to determine the level of knowledge regarding the RICE method (Rest, Ice, Compression, Elevation) among 30 volleyball athletes (30% male, 70% female) at SMA Negeri 1 Sewon, Bantul, Yogyakarta. Data were collected from May 14–16, 2026, using a 29-item questionnaire. The results indicated that the athletes' overall knowledge was categorized as good (37% or 11 athletes) with an average score of 26.1. However, a gap in understanding across components was observed. While athletes highly mastered the Ice component (93% in the good category) , other components were still dominated by the moderate (cukup) category: Rest (53%) , Compression (37%) , and Elevation (47%). In conclusion, although the athletes' general knowledge is good, their technical understanding of rest, compression, and elevation requires improvement. Periodic practical training or clinical simulations conducted by the school and coaching staff are highly recommended.